Development of A. N. Terenin’s ideas at Tomsk State University: Stages and personalia - Mayer, Georgy V. 1948- (Russian physics journal)
The stages of development of molecular photonics at Tomsk State University are presented. It was A. N. Terenin's student, N. A. Prilezhaeva, who pioneered the Russian photochemistry and fostered the development of a Tomsk school of spectroscopists, at that time the only research team in the Asian part of Russia. In 1950, the research in the field of molecular spectroscopy and quantum chemistry of complex molecules was initiated by a Prilezhaeva's student, V. I. Danilova, who became a TSU Professor at a later date. Fundamental problems were posed and solved, which related the spectra and the electron shell structure with the physical-chemical properties of several classes of complex organic molecules. The generalizations made by Danilova were quite valuable for the theory of molecular spectra and helped forming her own scientific school in 1970-80s.